PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA POP-UP BOK TERHADAP KEMAMPUAN BERNALAR KRITIS SISWA KELAS 5 SD NEGERI BRUMBUNG - Putri Eka Rahmayati Putri; Duwi Nuvitalia; Suyitno (STKIP Subang, 2023)
One of the 21st century skills that students must have is the ability to reason critically. Critical reasoning can be defined as a cognitive process that involves a systematic and analytical examination of a problem. The aim of this research is to determine the effect of the Problem Based Learning learning model assisted by Pop-Up Book media on the critical reasoning abilities of fifth grade students in science subjects at Brumbung State Elementary School. This type of research is Quantitative using the Problem Based Learning model assisted by Pop-Up Book media. The science and science subject is a combination of 2 science and social studies subjects. Science and science learning needs to present a context that is relevant to the natural conditions and environment around students (Tim, 2021). The population in this study was class V students with a total of 30 students and the research sample was class V A and class V B students totaling 60 students. The sampling technique is the experimental class and the control class is with class A as the experimental class, class B as the control class. The research instrument used was questions in the form of descriptions. The results of hypothesis testing using the t-test formula are ????h???????????????????? = 16,000 >???????????????????????? = 2.042 with α = 0.05. This means that there is an influence of the Problem Based Learning learning model assisted by Pop-Up Book media on the critical reasoning abilities of fifth grade students at SD Negeri Brumbung.